Science-driven Accelerator Program for Climate-Smart Agribusinesses: IPSR Innovation Profile - Dahl, Hauke; Zulu-Hume, Mercy F. (2022)
The science-driven accelerator program for climate-smart agribusinesses is a business acceleration program focusing on business from the extended agricultural ecosystem, supporting them in their goals to achieve impact and commercial success at scale. Informed by the structure and dynamics of private sector-driven accelerators, the science-driven accelerator program in Zambia focuses on private sector companies that have the capacity to scale climate-smart agricultural innovations. The objective of this program is two-fold: on the one hand, it aims to scale the innovations to a wider target group; on the other hand, it aims to strengthen the commercial capacity of the private sector entities that are onboarded. As with regular accelerators, the program culminates in a demo-day in which the portfolio of agribusinesses is connected to a wide range of public, concessional, and private investors as well as potential market partners like agricultural corporations. This demo-day provides access to finance and other market linkages for the agri small- and medium- sized enterprise (SME) portfolio, hereby offering them the opportunity to grow their businesses and subsequently realize a higher impact of their climate-smart agriculture-related project activities.